Pelatihan Bahasa Inggris Berbasis Tenun Songket Lombok Bagi Penenun Songket UD. Undur Pasang di Desa Sukarara - Sri Sukarni; Lalu Purnama Zulkarnaen (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
Small and Middle entrepreneurs (UKM) who want their products to go international must have the ability to speak English. Therefore, every UKM must equip its workers with the ability to communicate in English. UD. Undur Pasang wants to expand its promotion not only to domestic tourist/songket buyers but also foreign tourists/songket buyers. The plan has not been implemented properly because the English language skills possessed by the weavers are still minimal. This community service aimed 1) to motivate the Lombok songket weavers UD. Undur Pasang to learn English; 2) that the weavers of UD. Undur Pasang understand that English is needed to expand the market for UD. Undur Pasang songket product; 3) to improve communication skills in English for UD. Undur Pasang weavers. To realize these three objectives, English training was held. The training participants were all of UD. Undur Pasang songket weavers as many as ten weavers. The training method is carried out through four stages, namely 1) introduction; 2) socialization; 3) implementation and 4) final evaluation. The result of the community service can be concluded that 1) songket weavers of UD. Undur Pasang has motivation to take part in English training; 2) the result of the training is applied by the weavers; 3) the participants’ ability in Lombok songket-based English is categorized as good and has an impact on the production and sales of Lombok songket produced by UD. Undur Pasang